Strength of materials a course for students. - Black, Peter, 1915- (Pergamon Press, 1966)
Strength of Materials: A Course for Students deals with theories of stress analysis. The book describes simple stress, strain, and strain energy and defines, with appropriate formulas, commonly used terms such as load, elasticity, tensile test, and temperature stresses. The text then analyzes the moment when an applied force bends a subject beam under different load conditions. The formula for the first and second moments of area and the formula for the first and second moments of mass are explained. The book also describes the unstrained or neutral plane when a bending moment acting on a par.